Designing an empirical audit of the learning organization - Karen E. Watkins; Victoria J. Marsick (Adult Education Research Conference, 1993)
In this paper, we describe our approach to studying the learning organization. We begin with our framework for understanding the learning organization, describe seven defining characteristics, and pose measures for each characteristic.